2016
DOI: 10.1016/j.molcel.2015.11.010
|View full text |Cite|
|
Sign up to set email alerts
|

Two FGF Receptor Kinase Molecules Act in Concert to Recruit and Transphosphorylate Phospholipase Cγ

Abstract: SUMMARY The molecular basis by which receptor tyrosine kinases (RTKs) recruit and phosphorylate Src Homology 2 (SH2) domain-containing substrates has remained elusive. We used X-ray crystallography, NMR spectroscopy, and cell-based assays to demonstrate that recruitment and phosphorylation of Phospholipase Cγ (PLCγ), a prototypical SH2 containing substrate, by FGF receptors (FGFR) entails formation of an allosteric 2:1 FGFR-PLCγ complex. We show that the engagement of pTyr-binding pocket of the cSH2 domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 40 publications
1
38
0
Order By: Relevance
“…PRE experiments were carried out on a selectively labeled 15 N tyrosine I707C mutant of FGFR2K conjugated with an MTSL spin label. MTSL labeling was carried out as previously described ( Huang et al, 2016 ). A 1 H/ 15 N HSQC spectrum was acquired for both the oxidized and reduced forms of the MTSL spin label.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…PRE experiments were carried out on a selectively labeled 15 N tyrosine I707C mutant of FGFR2K conjugated with an MTSL spin label. MTSL labeling was carried out as previously described ( Huang et al, 2016 ). A 1 H/ 15 N HSQC spectrum was acquired for both the oxidized and reduced forms of the MTSL spin label.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…[52] Therefore, DOCK studies were performed on an X-ray structure of nSH2 in complex with fibroblast growth factor receptor 2 (FGFR2; PDB ID: 5EG3). [53] As seen in and/or C-8 in compounds 6 and 7. Our previous study [7] reported that…”
Section: Docking Analyses For An Anticancer Effect Of Compound 10mentioning
confidence: 97%
“…The docked structure of compound 10 in complex with the X-ray structure coordinates of PLCγ1 (PDB ID: 5EG3). [53] (a) X-ray structure coordinates of a small FGFR2 peptide (PDB ID: 5EG3) and docked coordinates of 10 are both shown, and (b) only the docked coordinates of 10 are shown in the binding site of PLCγ1. P-TYR(769) in (a) is phosphorylated TYR residue of FGFR2, which phosphorylates nSH2 to activate PLCγ1 Similarly, brominated quinolines, 3,6,8-tribromoquinoline (5), TGI values between 20.4 and 52.7 μg/ml, except A549 cell line) have very strong antitumor effects against all tested cell lines (Table 1 and 2).…”
Section: Docking Analyses For An Anticancer Effect Of Compound 10mentioning
confidence: 99%
See 1 more Smart Citation
“…FGFs activate transmembrane tyrosine kinases and their coupled intracellular signalling pathways to stimulate biological activities and transduce external signals through the PI3K, MAPK, and phospholipase Cg (PLCg) pathways (Klagsbrun, 1990;Zhou et al, 2009;Francavilla et al, 2013;Huang et al, 2016). A dual-receptor system comprising a family of four receptor tyrosine kinases (FGFRs) and heparan sulfate proteoglycans (HSPGs) mediates the stimulation of cellular metabolism by FGFs.…”
Section: Fgf Fgfmentioning
confidence: 99%